Comparative Study of Legal Protection for Women Workers on Night Shifts (Between Indonesia and Germany) - Silvia Ratna Anzani; Ratih Damayanti (Universitas Negeri Semarang, 2025)
The increasing participation of women in the workforce, including night shifts, demands adequate legal protection. This study compares legal protections for female night shift workers in Indonesia and Germany using normative legal research with statutory and comparative approaches. Indonesian regulations, including Law No. 13 of 2003 and Ministerial Decree No. 224/MEN/2003, provide protection through limitations on night work, provision of nutritious food, and mandatory transportation. In Germany, laws such as the Mutterschutzgesetz, Arbeitszeitgesetz, and Arbeitsschutzgesetz emphasize preventive measures like medical assessments, work hour restrictions, and risk evaluations. The findings indicate that Germany offers more structured protection, particularly for pregnant or breastfeeding women, while Indonesia's implementation often faces challenges. Both countries have ratified CEDAW, but Germany has integrated international standards more comprehensively into national law. This study highlights the need for stronger enforcement and legal reform in Indonesia to ensure the rights and safety of female workers on night shifts are effectively protected.